Differential Transport of Escherichia coli Isolates Compared to Abiotic Tracers in a Karst Aquifer. Issue 1 (9th May 2019) - Bandy, Ashley M.; Cook, Kimberly; Fryar, Alan E.; Zhu, Junfeng
Abstract: Lack of filtration and rapid transport of groundwater and particulate matter make karst aquifers susceptible to bacterial contamination. This study utilized quantitative polymerase chain reaction (qPCR) to examine the transport and attenuation of two nonvirulent isolates of Escherichia coli ( E. coli ) in relation to traditional groundwater tracers (rhodamine WT dye and 1‐µm diameter latex microspheres) in a karst‐conduit aquifer in central Kentucky. Bacterial isolates were labeled with stable isotopes ( 15 N and 13 C). All tracers were detected more than 6 km downstream from the injection site and demonstrated overlapping breakthrough curves, with differential transport observed between the two bacterial strains. The E. coli isolate containing the kps gene (low attachment) arrived at sampling sites 1.25 to 36 h prior to the bacterial isolate containing the iha gene (high attachment) and was detected in samples collected following storm events in which the iha isolate was not detected. The storage potential of contaminants within karst systems was demonstrated by the remobilization of all tracers during storm events more than 1 month after injection. Bacteria‐sized microspheres were more easily remobilized during periods of increased discharge compared to other tracers. The study demonstrated that molecular biology techniques such as qPCR can be utilized as a sensitive analysis of bacterial tracers in karst aquifers and may prove to be a more sensitive analytical technique than stable isotope analysis for field‐scale traces. Abstract : Article impact statement : Using molecular genetic techniques, we observed differential transport of bacterial strains compared to abiotic tracers in a karst aquifer.